A review on the chemistry, production, and technological potential of bio-based lubricants. (February 2018) - Zainal, N.A.; Zulkifli, N.W.M.; Gulzar, M.; Masjuki, H.H.
Abstract: The possible scarcity of oil and gas resources in the future (whether in quantity or areas of availability) is a major concern throughout the world. For this reason, governments all over the world are working on reducing their dependence on imported energy resources. Alternative energy resources such as bioethanol, biodiesel and biomass have gained prominence over the years in order to substitute petroleum-derived products. Bio-based lubricants have also gained importance as alternatives to conventional petroleum-based lubricants in various applications, especially the automotive industry. Despite the benefits of bio-based lubricants, these lubricants are still far from being practical substitutes. Since bio-based lubricants are typically produced from raw vegetable oils, these lubricants have poor cold flow properties as well as low thermo-oxidation and hydrolytic stability. However, these shortcomings can be addressed by modifying the vegetable oils chemically or incorporating additives into the oils. This review provides a detailed treatment on bio-based lubricants, the various vegetable oils used as the feedstocks for the production of bio-based lubricants, the physicochemical properties of bio-based lubricants, the processes used for chemical modification of vegetable oils, the lubrication properties of bio-based lubricants, as well as the various additives used to improve the properties of bio-based lubricants. It is believed that this review paper will provide useful insight to researchers and practioners in the field regarding bio-based lubricants.